Using fluency and comprehension instruction with struggling readers to improve student reading outcomes in English elementary schools - Maria Cockerill; Allen Thurston; Joanne O'Keeffe (International Journal of Educational Research Open, 2023)
This study reports results from a randomized controlled trial of a reading intervention program in English elementary schools implemented during Covid19. Trained staff delivered targeted reading fluency and comprehension instruction to small groups of eligible children aged 7–9 for at least 12-weeks. Twelve schools from four English districts with high socio-economic disadvantage participated, with a sample of 186 children. Positive effect sizes of +0.26 on overall reading scores were observed, on an independently designed standardised reading test. A process evaluation assessed implementation fidelity. This intervention shows excellent promise as a technique to improve overall reading (mainly through enhancing sentence level reading comprehension).